Wudu as Islamic Psychotherapy in Overcoming Emotions of Anger in Muslim Youth - Reza, Iredho Fani; Salsabila Nur Kamilah; Nasywa Syahira Oktaviani; Indri Seta Septadina; Magfiroh; Feby Hariani; Devy Puspita Sari; Lidya Puji Astuti; Putri Wulandari; Regista Ramadhania; Ferdian; M. Gozali; Alvin Masaiz (Indonesian Journal of Behavioral Studies, 2024)
This research aims to overcome angry emotions in Psychology students through Wudu psychotherapy. The research method used was pre-experimental using a one-group experimental design (One-Group Pretest-Posttest Design). The research respondents were Muslim youth who were students at the Faculty of Psychology, Raden Fatah State Islamic University, Palembang City, class of 2019. The respondents were 14 people, consisting of 3 men and 11 women. The instrument in this research uses a scaleanger leveland treatment monitoring records. The results of research analysis through the paired sample t-test showed a p value of 0.124 and a calculated t value of -1.644. From the pretest results, the score was 124.42 and the posttest results were 127.21. This shows the influence of wudu psychotherapy in controlling the emotion of anger in Psychology students at UIN Raden Fatah Palembang.